2015
DOI: 10.1055/s-0035-1563604
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection: One Disease, Variable Presentations, and Different Management Approaches

Abstract: Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome. It occurs predominantly among younger females, typically in the absence of atherosclerotic coronary artery disease. Presentations vary greatly and this condition can be fatal. Given its rarity, there are no management guidelines. We present six patients with SCAD with different presentations and treatment approaches as examples in our literature review. Two patients presented with ST elevation myocardial infarction (STEMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Participants in this study, the majority women, reported diverse symptoms of SCAD that varied in duration and intensity. Symptoms reported did not differ from those reported in extant literature on SCAD, 40 with chest pain as the chief symptom. 41 Other cardiac symptoms reported (eg, jaw pain, nausea, dizziness) are also consistent with the broader literature in women presenting with myocardial infarction.…”
Section: Discussionmentioning
confidence: 49%
“…Participants in this study, the majority women, reported diverse symptoms of SCAD that varied in duration and intensity. Symptoms reported did not differ from those reported in extant literature on SCAD, 40 with chest pain as the chief symptom. 41 Other cardiac symptoms reported (eg, jaw pain, nausea, dizziness) are also consistent with the broader literature in women presenting with myocardial infarction.…”
Section: Discussionmentioning
confidence: 49%
“…The discordance between clinical presentation and angiographic finding posed a unique challenge in therapeutic decision making. Unlike traumatic dissection of coronary arteries, more than half of SCAD heals spontaneously over time [ 2 , 7 ]. Due to this substantial rate of spontaneous healing, conservative medical management is recommended for patients who are hemodynamically stable with a minor dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The median time for SCAD recurrence is 2.8 years with an interval of 3 days to 12 years [ 9 ]. Hypertension and the use of calcium channel blockers are notable risk factors for SCAD recurrence [ 2 , 9 ]. Reported protective factor against SCAD recurrence was beta-blocker therapy [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, not properly diagnosed and treated it could lead to serious clinical consequences, including cardiac arrest and death. It is based on intimal tear or intramural bleeding of the vasa vasorum leading to the creation of a false lumen and to myocardial ischemia [ 2 ]. More frequently, it appears in young or middle-aged women [ 3 ].…”
mentioning
confidence: 99%